PENERAPAN ALGORITMA APRIORI MENENTUKAN KORELASI DATA PENJUALAN PUPUK (STUDI KASUS : PT. KARUNIA ROTORINDO TANI) - Ardianti, Ardianti; Novriyenni, Novriyenni; Nur Kadim, Lina Arliana (Jurnal Manajamen Informatika Jayakarta, 2023)
Currently information technology is developing so fast that the need for information is increasing. Information will be of no value if it is not managed properly. However, if the available data is large, conventional methods will no longer be able to analyze data to explore existing potentials. Therefore we need a method that can analyze, summarize and extract data to become useful information. In order to find out what fertilizers are often purchased by consumers, it is necessary to perform analysis techniques from data on sales using the Apriori algorithm method to determine combinations between item-sets from fertilizer sales transaction data at PT. Karunia Rotorindo Tani. If T1 and P3 then BT1 with support value = 20% and 100% confidence and S*C value = 20% if the T1 soil type is (Alluvial Soil) then the customer will buy P3 fertilizer, namely (Organic Formula Palm Oil Specific Fertilizer) with the brand name the fertilizer that many of these customers buy is BT1 (BT_Kelapa Sawit). with a supporting value of 20%, a certainty value of 100%.